High-temperature-resistant anticorrosive high-solid-content coating for carbon steel and preparation method thereof
By optimizing the combination of epoxy modified silicone, temperature-resistant filler, aluminum silver paste and crosslinking additives in the coating system, combined with the catalytic effect of n-butyl titanate, a high-temperature corrosion-resistant high-solid content coating for carbon steel was prepared, which solved the problem of poor burst paint and secondary film formation performance of existing coatings at high temperatures, and achieved excellent salt spray resistance and high-temperature resistance of the coating.
Patent Information
- Application Number
- CN202411767978.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
AI Technical Summary
The existing high-temperature anti-corrosion coatings are explosively painted when they exceed 550℃, which cannot meet the actual application needs of high-temperature places. The secondary film formation performance is poor, which is prone to powder loss and paint removal, affecting product quality.
By optimizing the combination of epoxy modified silicone, temperature-resistant filler, aluminum silver paste and crosslinking additives in the coating system and its addition amount control, a high-temperature anti-corrosion-resistant high-solid coating for carbon steel was prepared. The combination of epoxy modified silicone 1 of 150-650cp and epoxy modified silicone 2 of 50-150cp is used, and n-butyl titanate is introduced as a catalyst to promote crosslinking and curing.
The coating provided by the coating formed after curing the surface of the carbon steel plate has excellent salt spray resistance and high temperature corrosion resistance. It can maintain excellent appearance and corrosion resistance after baking at 600°C, meeting the practical application needs of high temperature places.
Smart Images

Figure BDA0005169484160000041 
Figure BDA0005169484160000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high temperature resistant anticorrosion coatings, and specifically to a high temperature resistant anticorrosion high solid content coating for carbon steel and a preparation method thereof. Background Art
[0002] High temperature resistant anti-corrosion coatings are mainly used in high temperature places such as steel chimneys, high temperature pipelines, high temperature furnaces, oil cracking devices and military equipment. The purpose is to delay the thermal oxidation corrosion of metal equipment such as steel at high temperature and ensure the long-term use of the equipment. However, the existing anti-corrosion coating products can generally only achieve anti-corrosion performance in the temperature range of 350℃-450℃. If the temperature exceeds 550℃, interlayer paint explosion will occur, which cannot meet the actual application requirements. And the secondary film-forming performance of the coating is poor. After the secondary film-forming at a high temperature of 350℃, it is easy to fall off and peel off the paint, which seriously affects the product quality. In addition, traditional high temperature resistant coatings are prone to color difference (silver paint turns yellow, matte black paint loses gloss) at high temperatures, affecting the appearance. For example, a high temperature resistant anti-corrosion coating and its preparation method disclosed in a Chinese patent application (authorization announcement number is CN102719191B) improves the high temperature resistance of the coating by optimizing the combination of primer and topcoat, but increases the construction complexity. Therefore, it is of great practical significance to provide a high temperature resistant and anti-corrosion high solid content coating for carbon steel to solve the above problems. Summary of the invention
[0003] In order to solve the above problems, the present invention provides a high-temperature resistant and anti-corrosion high-solid coating for carbon steel. The product has low cost, is easy to construct, is resistant to high temperatures, and can maintain excellent anti-corrosion properties after being resistant to high temperatures. It meets the actual application needs of high-temperature places such as steel chimneys, high-temperature pipelines, high-temperature furnaces, petroleum cracking devices and military equipment, and is easy to apply and promote.
[0004] On the one hand, the present invention provides a high-temperature resistant and anti-corrosion high-solid coating for carbon steel. The raw materials for its preparation include at least the following components, by weight: 30-50 parts of epoxy-modified silicone, 10-20 parts of aluminum silver paste, 0.8-1.5 parts of rheological additive, 10-20 parts of heat-resistant filler, 10-15 parts of solvent, 3-10 parts of pigment, and 3-5 parts of cross-linking additive.
[0005] As a preferred technical solution, the viscosity of the epoxy-modified silicone at 25±2°C (rotor No. 63, 17 r / min) is 50-1000 cp, preferably 150-650 cp of epoxy-modified silicone 1 (Quark SH-201) and 50-150 cp of epoxy-modified silicone 2 (Quark SH-214).
[0006] Preferably, the mass ratio of the epoxy-modified silicone 1 to the epoxy-modified silicone 2 is (0.5-1.5):1, preferably 1:1.
[0007] As a preferred technical solution, the mass ratio of the aluminum-silver paste and the temperature-resistant filler is (15-17):(10-15), preferably 15:12.
[0008] As a preferred technical solution, the mass proportion of non-volatile matter in the aluminum-silver paste is 60-70%.
[0009] As a preferred technical solution, the median diameter of the aluminum-silver paste is 10-18 μm.
[0010] As a preferred technical solution, the specific gravity of the aluminum-silver paste is 1.4-1.8, preferably 1.42.
[0011] As a preferred technical solution, the aluminum-silver paste is selected from at least one of Xuyang 2310, 2502, 2501, 2612, and 2618, preferably Xuyang 2502, with a non-volatile content of 65±2%, a median diameter of 13 μm, and a specific gravity of 18000.
[0012] As a preferred technical solution, the temperature-resistant filler is selected from DST series composite ceramic powders, including at least one of DST-8001, DST-8002, DST-8003, DST-8011, DST-8012, and DST-8013.
[0013] Preferably, the temperature-resistant filler is DST-8013, which is sourced from Jiangxi Dishi Mineral Fiber Technology Co., Ltd.
[0014] As a preferred technical solution, the solvent is selected from at least one of ethylene glycol monobutyl ether, propylene glycol methyl ether, dipropylene glycol dimethyl ether, ethanol, and isopropanol, preferably ethylene glycol monobutyl ether.
[0015] As a preferred technical solution, the pigments include at least white pearlescent and aluminum phosphate anti-rust pigments.
[0016] Preferably, the mass ratio of the white pearlescent pigment to the aluminum phosphate anti-rust pigment is (0.8-1.5):1, preferably 1:1.
[0017] As a preferred technical solution, the rheological additive is organic bentonite, and the particle size of the organic bentonite is 0.5-3 μm. Preferably, the rheological additive is selected from at least one of BP-136A, BS-2BF, BS-1C, BS-2B, HFGEL-321, GARAMITE 1958, HFGEL-170, and BENTONE SD-1, preferably BENTONE SD-1 (Hemmingsdeqian).
[0018] As a preferred technical solution, the cross-linking auxiliary agent is n-butyl titanate or amino resin, preferably n-butyl titanate.
[0019] The present invention optimizes the combination of epoxy-modified silicone, heat-resistant filler, aluminum paste and cross-linking auxiliary agent in the coating system and controls the amount of addition. The high-temperature resistant and anti-corrosion high-solid coating synthesized based on a specific process meets the application requirements of carbon steel, has increased convenience of use, and has excellent comprehensive performance of the coating after cross-linking and curing. In particular, a combination of 150-650cp epoxy-modified silicone 1 and 50-150cp epoxy-modified silicone 2 is used, and other raw materials in the system are matched, so that the coating formed after the provided coating is cured on the surface of the carbon steel plate has excellent salt spray resistance, and can maintain excellent appearance and anti-corrosion performance after baking at 600°C. Further, by controlling the mass ratio of aluminum paste and heat-resistant filler in the system to (15-17): (10-15), matching the non-volatile matter, median diameter, specific gravity control of aluminum paste and the selection of heat-resistant filler, the salt spray resistance and heat resistance of the cured coating are further guaranteed. In addition, the present invention initially used conventional amino resins for subsequent cross-linking, but in the actual testing process, it was found that the temperature resistance and salt spray resistance of the cross-linked and cured coating needed to be further improved. The inventors unexpectedly discovered during the exploration that by introducing n-butyl titanate as a catalyst, the epoxy-modified silicone combination in the system can be promoted to fully cross-link and cure to obtain a coating with excellent high temperature resistance and salt spray corrosion resistance, and the on-site operation time is short, which better meets the actual application needs.
[0020] The coating provided by the present invention has high solid content, low VOC, simple and easily available raw materials, is more environmentally friendly, and is easy to realize large-scale industrial production and application promotion.
[0021] On the other hand, the present invention provides a method for preparing a high-temperature resistant and anti-corrosion high-solid coating for carbon steel, which comprises at least the following steps: adding epoxy-modified silicone to a 40-60wt% solvent and stirring and mixing, adding a heat-resistant filler, a pigment, and a rheological additive and stirring and mixing to obtain a mixture; stirring and mixing aluminum silver paste and the remaining solvent to obtain a premix, adding the premix to the mixture and stirring and mixing to obtain a coating main agent, and adding a cross-linking auxiliary agent and stirring and mixing to obtain the coating when in use.
[0022] As a preferred technical solution, the preparation method of the high-temperature resistant and anti-corrosion high-solid coating for carbon steel comprises the following steps: adding epoxy-modified silicone to a 40-60wt% solvent and stirring and mixing, controlling the stirring speed to 900-1000r / min, adding a temperature-resistant filler, a pigment, and a rheological additive and stirring and mixing for 30-60min to obtain a mixture; stirring and mixing the aluminum silver paste and the remaining solvent at 500-700r / min for 15-30min to obtain a premix, adding the premix to the mixture, stirring and mixing at 500-700r / min for 30-60min to obtain a coating main agent, and adding a cross-linking auxiliary agent and stirring and mixing when using.
[0023] Beneficial Effects
[0024] 1. The present invention provides a high-solid-content high-temperature-resistant and anti-corrosion coating for carbon steel. The product has low cost, is easy to construct, is resistant to high temperatures, and can maintain excellent anti-corrosion properties after being resistant to high temperatures. It meets the actual application needs of high-temperature places such as steel chimneys, high-temperature pipelines, high-temperature furnaces, petroleum cracking devices, and military equipment, and is easy to apply and promote.
[0025] 2. The present invention optimizes the combination of epoxy-modified silicone, heat-resistant filler, aluminum paste and cross-linking aid in the coating system and controls the amount of addition. The high-temperature resistant and anti-corrosion high-solid coating synthesized based on a specific process meets the application requirements of carbon steel, increases ease of use, and has excellent comprehensive performance of the coating after cross-linking and curing.
[0026] 3. The present invention adopts a combination of 150-650cp epoxy-modified silicone 1 and 50-150cp epoxy-modified silicone 2, and coordinates other raw materials in the system, so that the coating formed after the provided coating is cured on the surface of the carbon steel plate has excellent salt spray resistance and can maintain excellent appearance and anti-corrosion performance after baking at 600°C.
[0027] 4. The present invention further ensures the salt spray resistance and temperature resistance of the cured coating by controlling the mass ratio of aluminum paste and heat-resistant filler in the system to (15-17): (10-15), and combining the non-volatile matter, median diameter, specific gravity control of the aluminum paste and the selection of heat-resistant filler.
[0028] 5. The present invention introduces n-butyl titanate as a catalyst to promote the epoxy-modified silicone combination in the system to fully cross-link and cure to obtain a coating with excellent high temperature resistance and salt spray corrosion resistance, thereby better meeting practical application requirements. DETAILED DESCRIPTION
[0029] Examples 1-5
[0030] Embodiments 1-5 of the present invention provide a high-temperature resistant and anti-corrosion high-solid coating for carbon steel, and the formula is shown in Table 1 in parts by weight.
[0031] Table 1
[0032]
[0033] Note: “ / ” in Table 1 means the addition amount of the corresponding raw material is 0.
[0034] On the other hand, embodiments 1-5 of the present invention provide a method for preparing a high-temperature resistant and anti-corrosion high-solid coating for carbon steel, comprising the following steps:
[0035] Add epoxy-modified silicone to 50wt% of solvent and stir and mix, control the stirring speed to 1000r / min, add heat-resistant filler, pigment, and rheological additive, stir and mix for 40 minutes to obtain a mixture; stir and mix aluminum silver paste and the remaining solvent at 600r / min for 20 minutes to obtain a premix, add the premix to the mixture, stir and mix at 600r / min for 60 minutes to obtain a coating main agent, and add a cross-linking auxiliary agent and stir and mix when using.
[0036] Performance Testing
[0037] 1. Heat resistance: The coating provided in Examples 1-5 was sprayed onto the surface of a carbon steel plate, and after baking at 150°C for 1 hour, a test piece containing a 100 μm coating was placed in a muffle furnace and heated to 600°C with the furnace. After maintaining for 4 hours, the temperature was cooled with the furnace. After returning to room temperature (25°C), the surface state was observed. According to the national standard GB / T9286-1998, the adhesion of the paint film was tested using a crosshatch tester. The results are shown in Table 2.
[0038] 2. Salt spray resistance: The coating provided in Examples 1-5 was sprayed onto the surface of a carbon steel plate and baked at 150°C for 1 h to obtain a test piece containing a 100 μm coating. The test was performed in accordance with GB / T1771-1991 "Determination of neutral salt spray resistance of paints and varnishes". The results are shown in Table 2.
[0039] 3. Salt spray resistance (after 600°C temperature resistance): The coating provided in Examples 1-5 was sprayed onto the surface of the carbon steel plate, and the test piece containing a 100 μm coating was obtained after baking at 150°C for 1 hour. The test piece was then placed in a muffle furnace and heated to 600°C with the furnace. After maintaining for 4 hours, the temperature was cooled with the furnace. After returning to normal temperature (25°C), the salt spray resistance test was carried out according to Method 2. The results are shown in Table 2.
[0040] 4. Water resistance test: The coating provided in Example 1 was sprayed onto the surface of a carbon steel plate, and after baking at 150°C for 1 hour, a test piece containing a 100 μm coating was placed in a muffle furnace and heated to 600°C with the furnace. After maintaining for 4 hours, the temperature was cooled with the furnace. After returning to room temperature (25°C), the test was performed in accordance with the national standard for paint film water resistance test GB / T1733-1993. Specifically, the test piece was placed in 40°C water and continuously immersed at a constant temperature. After the test was completed, the state of the paint film was observed. The results are shown in Table 2.
[0041] 5. High temperature and high humidity resistance test: The coating provided in Example 1 was sprayed onto the surface of a carbon steel plate, and after baking at 150°C for 1 hour, a test piece containing a 100 μm coating was obtained. The test piece was tested in accordance with the national standard GB / T 1740-2007 for high temperature and high humidity resistance test of paint films. The plate was placed under the conditions of temperature 85°C / humidity 85%, and the surface condition of the plate was observed. The results are shown in Table 2.
[0042] 6. Hot and cold cycle test: The coating provided in Example 1 was sprayed onto the surface of a carbon steel plate and baked at 150°C for 1 hour to obtain a test piece containing a 100 μm coating. According to the national standard GB4893.7-85, a -40°C-85°C cycle test was performed with a conversion time of 15 minutes and a single cycle of 2 hours. The results are shown in Table 2.
[0043] 7. Antifreeze resistance test:
[0044] The coating provided in Example 1 was sprayed onto the surface of a carbon steel plate, and after baking at 150° C. for 1 h, a test piece containing a 100 μm coating was obtained. The test piece was tested in accordance with the national standard GB / T 1763-1979 for chemical resistance of paint films, and the test piece was immersed in an antifreeze solution for testing.
[0045] 8. Hardness test:
[0046] The coating provided in Example 1 was sprayed onto the surface of a carbon steel plate, and after baking at 150° C. for 1 h, a test piece containing a 100 μm coating was obtained, and the paint film hardness was tested according to the pencil method for paints and varnishes in accordance with GB / T 6739-2006.
[0047] Table 2
[0048]
Claims
1. A high-temperature resistant and anti-corrosion high-solid coating for carbon steel, characterized in that: The raw materials for its preparation include at least the following components by weight: 30-50 parts of epoxy-modified silicone, 10-20 parts of aluminum silver paste, 0.8-1.5 parts of rheological additive, 10-20 parts of heat-resistant filler, 10-15 parts of solvent, 3-10 parts of pigment and 3-5 parts of cross-linking additive.
2. The high temperature resistant and anti-corrosion high solid coating for carbon steel according to claim 1, characterized in that: The epoxy-modified silicone has a viscosity of 50-1000 cp at 25±2°C.
3. The high temperature resistant and anti-corrosion high solid coating for carbon steel according to claim 2, characterized in that: The mass ratio of the aluminum-silver paste to the heat-resistant filler is (15-17): (10-15).
4. The high temperature resistant and anti-corrosion high solid coating for carbon steel according to claim 3, characterized in that: The mass proportion of non-volatile matter in the aluminum-silver paste is 60-70%, the median diameter of the aluminum-silver paste is 10-18 μm, and the specific gravity of the aluminum-silver paste is 1.4-1.
8.
5. The high temperature resistant and anti-corrosion high solid coating for carbon steel according to claim 4, characterized in that: The solvent is selected from at least one of ethylene glycol monobutyl ether, propylene glycol methyl ether, dipropylene glycol dimethyl ether, ethanol and isopropanol.
6. The high temperature resistant and anti-corrosion high solid coating for carbon steel according to claim 5, characterized in that: The pigments at least include white pearlescent pigments and aluminum phosphate anti-rust pigments.
7. The high temperature resistant and anti-corrosion high solid coating for carbon steel according to claim 6, characterized in that: The rheological additive is organic bentonite, and the particle size of the organic bentonite is 0.5-3 μm.
8. The method for preparing the high temperature resistant and anti-corrosion high solid content coating for carbon steel according to claim 7, characterized in that: The cross-linking auxiliary agent is n-butyl titanate or amino resin.
9. A method for preparing a high temperature resistant and anti-corrosion high solid coating for carbon steel according to any one of claims 1 to 8, characterized in that: At least the following steps are included: Add epoxy modified silicone to 40-60wt% solvent and stir and mix, add heat resistant filler, pigment and rheological additive and stir and mix to obtain a mixture; stir and mix aluminum silver paste and the remaining solvent to obtain a premix, add the premix to the mixture and stir and mix to obtain a coating main agent, and add a cross-linking auxiliary agent and stir and mix to obtain the coating when using.
10. The method for preparing the high temperature resistant and anti-corrosion high solid content coating for carbon steel according to claim 9, characterized in that: The following steps are involved: Add epoxy modified silicone to 40-60wt% solvent and stir and mix, control the stirring speed to 900-1000r / min, add heat resistant filler, pigment and rheological additive and stir and mix for 30-60min to obtain a mixture; stir and mix aluminum silver paste and the remaining solvent at 500-700r / min for 15-30min to obtain a premix, add the premix to the mixture, stir and mix at 500-700r / min for 30-60min to obtain a coating main agent, and add a cross-linking auxiliary agent and stir and mix when using.
Citation Information
Patent Citations
High-temperature-resistant anticorrosive paint and preparation method thereof
CN102719191B
Preparation and coating technology of high-temperature-resisting anticorrosive coating
CN108117834A
Normal-temperature self-drying water-based aluminum powder high-temperature-resistant coating as well as preparation method and application thereof
CN116445077A
Cited By
Heat-resistant self-repairing zinc silicate anticorrosive paint and preparation method thereof
CN120173436A